The Portrayal Of Assamese Rural Life In The Story ‘Sakha Damodar’ By Lakshminandan Bora: A Discussion (Journal of Namibian Studies : History Politics Culture, 2023)
Assamese fiction, which developed in the pages of Jonaki and Avahan, gained notable popularity in the pages of the Ramdhenu era in the post-war period. Many storytellers established themselves during this era and enriched Assamese literature. Among them is Lakshminandan Bora. There are many different types of short stories in Assamese literature. Lakshminandan Bora, who wrote and produced many literary works during the Ramdhenu period, based most of his short stories on the “accurate portrayal of Assamese rural society.” Many stories are written against the background of rural life in Assamese literature. Still, the agrarian society depicted in the short stories of Lakshminandan Bora is full of tangible and realistic experiences. Bora’s stories are based on rural life and represent various aspects of society, such as laughter, tears, hopes and disappointments, happiness and sorrow, customs, love, and problems. “Sakha Damodar” is one of the significant short stories explicitly portraying that society. The story is set against the backdrop of Assamese rural life and paints a perfect picture of the rural community. This study attempts to discuss the various aspects of Assamese rural society, such as customs, rituals, and food, and how those are reflected in the story.